Eruption cyst in a patient with microcephaly: a case report - Couto,Graziane Ribeiro (2020)
Abstract The aim of this paper is to report the clinical case of a 3-year and 7-month-old male child with microcephaly who had multiple eruption cysts, and to discuss the adopted procedures. The diagnosis of eruption cyst was concluded based on the clinical and radiographic characteristics. The treatment proposed was a surgical incision of the eruption cysts with the patient under general anesthesia. However, due to health reasons, the patient could not have the procedure performed, and, after four months, seven of the eight eruption cysts had regressed with teeth eruption; therefore, no surgical intervention was needed. Regarding the remaining eruption cyst, the therapy adopted was his mother monitoring the condition. It is possible to personalize eruption cyst treatment by monitoring the lesion until its eventual spontaneous disappearance, without any type of intervention.